2021
DOI: 10.20473/bhsj.v4i2.26619
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulator Effect of Lemongrass Extract (Cymbopogon nardus L.) to Increase Immune Cells as a Precaution Against SARS-CoV-2

Abstract: Introduction: In humans, Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) can damage some tissue when the immune systems was decrease. Natural product from the plant often used to improve immune response against microorganism including virus. This study aimed to determine the potential antioxidant of lemongrass extract (C . nardus) with various dosage that can provide immunomodulatory effects and find an optimal dosage to be used.  Methods: The method used observasional analytic, using animal model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…6 In addition, some secondary metabolites perform the function of inflammatory modulators of intestinal desease. 7 Citronella is a rhizome plant which is widely used and proven for its efficacy. Phytochemical screening of citronella grass showed that it contains flavonoids, terpenoids, saponin and tannin.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, some secondary metabolites perform the function of inflammatory modulators of intestinal desease. 7 Citronella is a rhizome plant which is widely used and proven for its efficacy. Phytochemical screening of citronella grass showed that it contains flavonoids, terpenoids, saponin and tannin.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, immunomodulator from natural compounds (phytochemical) is preferable because it has lower toxicity (12,13). The most common phytochemicals that can modulate immune response are flavonoids, flavanols, quinones, glycosides, polysaccharides, terpenoids, alkaloids, phenolics, saponins, various bitter, vitamin C, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, C. nardus, one kind lemongrass, is known for its antioxidant activity and effective scavenging mechanisms for free radicals through its potent flavonoid compound. 10,11 Therefore, this research investigated the potential protective of C. nardus extract on the male reproductive system after being induced by lead acetate. The parameters of measurement were morphology, concentration, and motility of spermatozoa.…”
Section: Introductionmentioning
confidence: 99%